Analisis Potensi Fisik Pulau Laki untuk Kesesuaian Wisata Pantai di Kepulauan Seribu Tahun 2018 - Alvin, Fauzi; Suroso, Suroso; Moch., Arifien (Geo-Image, 2019)
This study purposed to knowing physical potential of Laki Island and knowing the suitability of beach tourism of Laki Island . This research method is quantitative descriptive. Data analysis using IKW tourist suitability index with scoring techniques several variables used for suitability of beach tourism. The results showed that from 3 beach observation stations on Pulau Laki; a) station 1 has a score of 43 and IKW is 75.43%, b) station 2 has a score of 51 and IKW is 89.77%, and c) station 3 has a score of 37 and IKW is 64.91%.. The calculation of the average beach tourism suitability index shows a percentage of 76.70%, based on the level of suitability in the appropriate category for beach tourism activities. The suggestion in this research is to clean the shrubs around the beach so that it can add to the beauty of the beach and also increase the flexibility for visitors to move, handling dangerous biota, by giving warnings to visitors, overcome the availability of fresh water can be anticipated by bringing the water from the Tanjung Kait dock.